2021
DOI: 10.3390/brainsci11070869
|View full text |Cite
|
Sign up to set email alerts
|

Probable Pain on the Pain Assessment in Impaired Cognition (PAIC15) Instrument: Assessing Sensitivity and Specificity of Cut-Offs against Three Standards

Abstract: Observational pain scales can help to identify pain in persons with dementia who may have difficulty expressing pain verbally. The Pain Assessment in Impaired Cognition-15 (PAIC15) covers 15 items that indicate pain, but it is unclear how probable pain is, for each summed score (range 0–45). We aimed to determine sensitivity and specificity of cut-offs for probable pain on the PAIC15 against three standards: (1) self-report when able, (2) the established Pain Assessment in Advanced Dementia (PAINAD) cut-off of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
1
10
1
1
Order By: Relevance
“…For timely pain management, caregivers are in desperate need of a way to interpret the nonverbal communications of patients with dementia. 13 Pain is highly prevalent in patients with dementia who are nonverbal. Chronic pain is still undertreated in such patients because of changes in their perception and expression of pain.…”
Section: Characteristics Of Patients With Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…For timely pain management, caregivers are in desperate need of a way to interpret the nonverbal communications of patients with dementia. 13 Pain is highly prevalent in patients with dementia who are nonverbal. Chronic pain is still undertreated in such patients because of changes in their perception and expression of pain.…”
Section: Characteristics Of Patients With Dementiamentioning
confidence: 99%
“… 14 Near the end of life, patients with dementia might have increased pain when resting. 13 Pain severity could predict a decline in daily living functioning for those patients. 15 A systematic review showed strong scientific evidence for five body movements as pain indicators in older adults who had cognitive impairments and who could not self‐report pain: physical aggression, agitation (restlessness), guarding, rubbing, and rigidity.…”
Section: Characteristics Of Patients With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The articles included in this Special Issue focus on pain outcomes and pain responses in varies types and pathologies of cognitive impairments, ranging from individuals with intellectual disabilities [ 1 , 2 , 3 ] to older adults with varying degrees of cognitive impairments [ 4 , 5 , 6 , 7 ] and more severe forms of dementia [ 8 ]. Moreover, about half of the articles have a clear clinical perspective, with investigations focused on the reliability [ 9 ] and clinical cut-off scores [ 8 ] of observational pain assessment scales as well as reflections on the pain management and pharmacological treatment of pain in younger and older individuals with cognitive impairments [ 1 , 7 ]. Other articles applied controlled experimental pain stimuli to compare pain sensitivity between different pathologies of cognitive impairments [ 2 , 4 ].…”
mentioning
confidence: 99%
“…Across all articles, it becomes evident that pain is still often overlooked in individuals with cognitive impairments and that observational pain assessment tools are necessary to improve this situation in these vulnerable individuals. The articles included also show promising findings, namely that these observational pain assessment scales allow for a reliable pain assessment that is relatively consistent across different regions in Europe, across different language versions, and across different pathologies [ 3 , 4 , 8 , 9 ]. Moreover, it also becomes apparent across articles that cognitive impairment is not necessarily associated with a decrease in pain responsiveness to noxious stimuli; in contrast, several articles point to an increase in pain responses in individuals with cognitive impairments [ 2 , 4 , 5 ].…”
mentioning
confidence: 99%